The Effect of Live Streaming Interactivity and Influencer Credibility on Purchase Decisions of TikTok Shop Users in Palopo City - nirmala nirmala; Muhammad Kasran; Putri Dewintari (Jurnal Studi Manajemen dan Bisnis, 2026)
The purpose of this study is to explore how consumer purchasing decisions on the TikTok Shop platform in the Palopo area are influenced by live streaming interactivity and trust in influencers. This research is quantitative in nature and primarily uses survey methods. A total of 109 active TikTok Shop users participated in this study. Questionnaires were used to collect data, and SPSS version 21 software was used to process the data using multiple linear regression techniques. The main conclusion shows that, both individually and collectively, live streaming interactivity and trust in influencers significantly enhance purchasing decisions. These two independent factors explain 60.9% of the variation in purchasing decisions, according to the coefficient of determination (R2) of 0.609. Implications from these results suggest that increasing the level of interactivity and the trustworthiness of influencers will raise the likelihood of consumers making purchases through TikTok Shop.